2020
DOI: 10.5604/01.3001.0014.1261
|View full text |Cite
|
Sign up to set email alerts
|

Review and characteristics of 585 salivary gland neoplasms from a tertiary hospital registered in the Polish National Major Salivary Gland Benign Tumors Registry over a period of 5 years: a prospective study

Abstract: <b>Introduction:</b> A Polish National Major Salivary Gland Benign Tumors Registry (SGR) is a report of benign salivary gland neoplasms (SGNs) from 26 different centres in Poland, introduced in 2014. The aim of this study is to analyze demographic characteristics and clinico-pathological factors of benign SGNs treated in large tertiary institutions and to determine possible correlations between selected variables. <br><b>Material and method:</b> Analysis of 585 patients recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Based on these, the TNM classification of malignant tumors is carried out, as well as the guidance of the surgical approach technique. [56,57] In the present study, we observed an association of the surgical technique depending on the maximum diameter of the lesion.…”
Section: Diagnosissupporting
confidence: 60%
“…Based on these, the TNM classification of malignant tumors is carried out, as well as the guidance of the surgical approach technique. [56,57] In the present study, we observed an association of the surgical technique depending on the maximum diameter of the lesion.…”
Section: Diagnosissupporting
confidence: 60%
“…However, our work has some limitations, as we were only able to analyse variables that were available and fully documented by all Polish Salivary Network Database mem-bers [34][35][36]. This meant that variables such as imaging outcomes could not be included because each department had different equipment, producing separate imaging protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Although our work has some limitations, as we were only able to analyse variables that were available and fully documented by all Polish Salivary Network Database members [33,34,35]. This meant that variables such as imaging outcomes could not be included because each Department had different equipment, producing separate imaging protocols.…”
Section: Discussionmentioning
confidence: 99%